Construction and demolition waste management by Baixo Alentejo municipalities - Ramos, Mário (2021)
This report presents the results of a participatory workshop conducted with municipal technicians in the Baixo Alentejo region of Portugal, emphasizing the importance of a common regulatory framework for construction and demolition waste (CDW) management at the local level.